“New Alien Mediterranean Biodiversity Records” (March 2021) - ORFANIDIS, SOTIRIS; ALVITO, ANDREA; AZZURRO, ERNESTO; BADREDDINE, ALI; BEN SOUISSI, JAMILA; CHAMORRO, MANUEL; CROCETTA, FABIO; DALYAN, CEM; FORTIČ, ANA; GALANTI, LUCA; GEYRAN, KEMAL; GHANEM, RAOUIA; et al. (Mediterranean Marine Science, 2021)
This article includes twenty (20) new records of alien and cryptogenic species in the Mediterranean Sea, belonging to six (6) Phyla (Rhodophyta, Tracheophyta, Mollusca, Arthropoda, Bryozoa, and Chordata) distributed from the Eastern Mediterranean to the Sea of Alboran. The records are reported from nine (9) countries and can be classified into two categories: new records for the Mediterranean Sea and new records of non-indigenous species expanding within the Mediterranean Sea. The first category includes the gastropod Turbo radiatus from Lebanon coasts, the portunid crab Charybdis (Charybdis) natator from Tunis southern lagoon, the mollusc Thuridilla mazda from South Spain, and the nudibranch Okenia picoensis from the Alboran coasts of Spain and from Malta. The second category includes the bivalve Nudiscintilla cf. glabra from the Aegean coast of Turkey, the rhodophyte Colaconema codicola from the North Aegean coasts of Greece, the naked band gaper Champsodon nudivittis from the Sea of Marmara, Turkey. Also, the brachyuran Gonioinfradens giardi from the Greek Ionian waters, the codlet Bregmaceros nectabanus from the Croatian coasts of the Adriatic Sea, and the bryozoan Arbopercula tenella and copepod Parvocalanus crassirostris both from the Gulf of Trieste, Slovenian and Italian coasts, respectively. New records were also reported for the ascidian Distaplia bermudensis from brackish the Gulf of Naples, Italy, the damselfish Abudefduf cf. saxatilis and the seagrass Halophila stipulacea from Sardinia, Tyrrhenian Sea, and for the fish Paranthias furcifer from the harbour of Almeria, Alboran Sea, Spain. Through these records, an understanding of the expanding mechanisms and processes and, if possible, the development of mitigation measures within the region will be further facilitated.